ANALISIS KEBUTUHAN PADA SKILL MENULIS: APA YANG SESUNGGUHNYA SISWA BUTUHKAN UNTUK MATA KULIAH MENULIS? - Desi Wijayanti Ma'rufah; Muflihah Muflihah; Ulil Awaliyah (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
This study aims to investigate the needs of students in writing skills. In particular, this research attempts to explore the present situation, the target, and the learning needs for the writing course. Need analysis is conducted for deciding the goals and the objectives of the upcoming curriculum and for ensuring that the curriculum content ties the students’ needs. A descriptive method was employed in this study. A questionnaire was used for collecting the data which then analyzed and described qualitatively. The respondents of this research were 176 students of English Education Department students who are mostly in the second semester. The results show that; firstly, in the present situation analysis, most of the students admitted that they were in the intermediate level of English; specifically, most of them have fair proficiency in writing. Next, in the target situation analysis, writing skill is the secondary need of the students in which grammar is the most priority needed by the students to be improved. Next, the students’ purposes in learning English are to be a teacher/lecturer, translator, and tourism guide. Most of the students are more enjoyable for learning in the classroom that should be consisted of not more than 30 students. Thirdly, in the learning needs analysis, the students were interested to learn writing using discussion. For doing the writing task, the students require to have individual work. The learning media that is the most needed is PowerPoint presentation. In addition, the most important learning source that the students need is a hand-out and the topics of the material are about issues in Indonesia. Finally, the results of this research are expected to contribute to the curriculum development at the English Education Department of UIN SAIZU.